Hydroxychloroquine as a Chemoprophylactic Agent for COVID-19: A Clinico-Pharmacological Review - Agarwal, Mudit; Ranjan, Piyush; Baitha, Upendra; Mittal, Ankit (Frontiers in Pharmacology, 2020)
Hydroxychloroquine has gained much attention as one of the candidate drugs that can be repurposed as a prophylactic agent against SARS-CoV-2, the agent responsible for the COVID-19 pandemic. Due to high transmissibility and presence of asymptomatic carriers and presymptomatic transmission, there is need for a chemoprophylactic agent to protect high risk population. In this review, we dissect the currently available evidence on hydroxychloroquine prophylaxis from a clinical and pharmacological point of view. In vitro studies on Vero cells show that hydroxychloroquine effectively inhibits SARS-CoV-2 by affecting viral entry as well as viral transport via endolysosomes. However, this efficacy has failed to replicate in in vivo animal models as well as in most clinical observational studies and clinical trials assessing pre-exposure prophylaxis and post-exposure prophylaxis in healthcare workers. An analysis of the pharmacology of HCQ in COVID-19 reveals certain possible reasons for this failure- a pharmacokinetic failure due to failure to achieve adequate drug concentration at target site; and attenuation of its inhibitory effect due to the presence of TMPRSS2 in airway epithelial cells. Clinical trials should be designed taking into account the effect of these factors. Current trials focus on healthcare workers, and there is a need for trials targeting vulnerable groups in the community setting.